An alternative in the diagnosis and monitoring of Diabetes Mellitus to detection via biomarkers: a systematic review (Research, Society and Development, 2021)
Diabetes Mellitus is a highly prevalent metabolic disorder of the beta-pancreatic cells worldwide. The diagnosis currently occurs by using glycemic tests combined with the dosage of some biomarkers. Therefore, this paper aims to analyze clinical techniques for diagnosis and therapeutic monitoring of diabetes mellitus, highlighting alternative and compensatory forms. A systematic review was carried out via survey in SCIELO, PUBMED and LILACS platforms. The keywords used were combined in English and Portuguese. The time frame established includes the years 2010 to 2021. Finally, data were organized via Prisma statement flowchart, summary table, and GRADE evidence scale. In their research, the authors reported that the glycated hemoglobin should not be used in screening for pre-diabetes, besides having interferences. As for the glycated albumin, it will act as a substitute and helps in detecting complications arising from diabetes, in the same way as the 1.5 anhydroglucitol, in addition, it can detect the chances of mortality from the disease. And finally, anti-GAD and C-peptide help in the detection of type 1 diabetes, evaluation of insulin therapy, and research into the development of autoimmune diseases. Although biomarkers have great benefits, the use of glycemic tests is still preferable. Finally, through this study it is possible to verify that biomarkers are alternative methodologies that can still be improved, are effective in detecting the disease, but are not yet used unattended or applied effectively in gestational diabetes. Moreover, they not only alert to the risks of developing complications but are also surgical parameteres.